Plant community dynamics of lomas fog oasis of Central Peru after the extreme precipitation caused by the 1997-98 El Niño event - Tovar C. (2018)
This work was supported by Concejo Nacional de Ciencias y Tecnología (CONCYTEC)—Peru; Universidad Nacional Agraria La Molina. The funders had no role in study design, data collection and analysis, decision to publish, or preparation of the manuscript.